Three new species of Commelina (Commelinaceae) from the central part of Mexico - López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; Ceja-Romero, Jacqueline (Instituto de Ecología, A.C., 2009)
Commelina congestispatha López-Ferrari, Espejo et Ceja, Commelina ramosissima López-Ferrari, Espejo et Ceja, and Commelina queretarensis López-Ferrari, Espejo et Ceja, are described and illustrated as new in this paper. The former is known from the states of Michoacán, Guanajuato and Querétaro, the second was collected in the states of Guanajuato, Querétaro and Michoacán, and the last one comes from Querétaro in the municipios of San Joaquín and Landa de Matamoros.